The Mexican Revolution in Chicago : Immigration Politics from the Early Twentieth Century to the Cold War - Flores, John H., 1977- (Latinos in Chicago and the Midwest., 2018)
Few realize that long before the political activism of the 1960s, there existed a broad social movement in the United States spearheaded by a generation of Mexican immigrants inspired by the revolution in their homeland. Many revolutionaries eschewed U.S. citizenship and have thus far been lost to history, though they have much to teach us about the increasingly international world of today. John H. Flores follows this revolutionary generation of Mexican immigrants and the transnational movements they created in the United States. Through a careful, detailed study of Chicagoland, the area in and around Chicago, Flores examines how competing immigrant organizations raised funds, joined labor unions and churches, engaged the Spanish-language media, and appealed in their own ways to the dignity and unity of other Mexicans. Painting portraits of liberals and radicals, who drew support from the Mexican government, and conservatives, who found a homegrown American ally in the Roman Catholic Church, Flores recovers a complex and little known political world shaped by events south of the U.S border.